To the bright edge of the world [large type] : a novel - Ivey, Eowyn (Thorndike Press, 2016)
"In the winter of 1885, Lieutenant Colonel Allen Forrester sets out with his men on an expedition into the newly acquired territory of Alaska. Their objective: to travel up the ferocious Wolverine River, mapping the interior and gathering information on the region's potentially dangerous native tribes. With a young and newly pregnant wife at home, Forrester is anxious to complete the journey with all possible speed and return to her. But once the crew passes beyond the edge of the known world, there's no telling what awaits them. With gorgeous descriptions of the Alaskan wilds and a vivid cast of characters -- including Forrester, his wife Sophie, a mysterious Eyak guide, and a Native American woman who joins the expedition - TO THE BRIGHT EDGE OF THE WORLD is an epic tale of one of America's last frontiers, combining myth, history, romance, and adventure" -- Amazon.com.